The Influence of Gender and Study Duration on EFL Learners' Speaking Strategies Use - Dinsa, Mitiku Tasisa; Woldamariam, Getachew Seyoum; Dinsa, Dagne Tiruneh (Universitas Negeri Makassar, 2022)
AbstractThe speaking strategy use of students is perceived to be successful in L2 learning and competent English users. The aim of this study was to pinpoint the influence of gender differences on students' speaking strategies use. It also intended to identify the influence of study duration on students' speaking strategies use to learn speaking skill at Wolaita Sodo University, Ethiopia. The participants of the current study were 70 (34 female and 36 male) English major students in the Academic Year of 2020. A descriptive comparison design was utilized for this study. The data were collected from the targeted population using a questionnaire and interview whether gender and study duration influence students' speaking strategies use or not. The results denoted that there were significant relationships between females and males in employing speaking strategies to learn speaking skill. Gender has no an influence on students' speaking strategies use to exercise oral communication. However, the finding denoted that there was statistically a significant difference between second year and third year EFL students in using speaking strategies to promote their speaking proficiency. Study duration has an influence on students' speaking strategies use to train oral communication. Therefore, this study recommends learners should use appropriate speaking strategies based on their interest to promote their speaking proficiency; they must be trained and supported to employ different strategies develop their oral communication skills.